Increased Postoperative Fasting Glucose Is Associated With Unfavorable Outcomes in Patients Treated With Mechanical Thrombectomy Treatment - Shi, Zongjie; Guo, Shunyuan; Pan, Jie; Xu, Chao; Geng, Yu; Zheng, Sujie (Frontiers in Neurology, 2021)
Background and objective: Hyperglycemia on admission was associated with worse clinical outcomes after mechanical thrombectomy (MT) of acute ischemic stroke (AIS). We evaluated whether increased postoperative fasting glucose (PFG) was also related to poor clinical outcomes in patients who underwent MT treatment. Methods: Consecutive patients with large vessel occlusion underwent MT in our center were included. Admission glucose and fasting glucose levels after MT treatment were evaluated. Primary outcome was 90-day unfavorable outcomes (modified Rankin Scale score of 3–6). Secondary outcome was the rate of symptomatic intracranial hemorrhage (sICH) after MT treatment. The association of PFG and 90-day clinical outcome after MT treatment was determined using logistic regression analyses. Results: One hundred twenty seven patients were collected. The median postoperative fasting glucose level was 6.27 mmol/L (IQR 5.59–7.62). Fourteen patients (11.02%) had sICH, and fifty-eight patients (45.67%) had unfavorable outcomes at 90-day after MT. After adjustment for potential confounding factors, PFG level was an independent predictor of 90-day unfavorable outcome (OR 1.265; 95% CI 1.017–1.575; p = 0.035) and sICH (OR 1.523; 95% CI 1.056–2.195; p = 0.024) after MT. In addition, older age, higher baseline NIHSS score, and higher postoperative NLR were also associated with unfavorable outcomes at 90-day after MT treatment. Conclusions: Increased PFG is associated with unfavorable outcomes at 90-day and an increased risk of sICH in patients underwent MT treatment.